Ethical Politics in Classical Islamic Civilization: A Comparative Study of the Thoughts of Al-Mawardi and Al-Farabi - Karep, Karep (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2025)
This study aims to examine and compare the ethical political thought of two major figures in classical Islamic civilization, namely Al-Mawardi and Al-Farabi. Both lived in different socio-political contexts, yet both offered philosophical and normative foundations for the exercise of power within the Islamic tradition. Al-Mawardi, through his monumental work Al-Ahkam al-Sultaniyyah, emphasized the importance of the legality and stability of the caliphate institution based on the principles of sharia. Meanwhile, Al-Farabi, in Ara’ Ahl al-Madinah al-Fadilah, presents a philosophical-utopian approach to the ideal state led by al-rais al-awwal (the supreme leader) as the embodiment of the highest virtue. This study uses a qualitative approach with a literature review and comparative analysis of the primary works of the two figures. The results of the study show that Al-Mawardi is more normative-pragmatic and focuses on real political order, while Al-Farabi is more idealistic with a political philosophy influenced by the Greek-Islamic tradition. Despite their differences, both make important contributions to the conceptualization of political ethics in Islamic civilization and remain relevant in contemporary discourse on leadership and public ethics. These findings enrich the body of Islamic political science and encourage the revitalization of ethical values in political governance in the modern era.